Noninvasive quantification of oxygen saturation in the portal and hepatic veins in healthy mice and those with colorectal liver metastases using QSM MRI. Issue 4 (19th November 2018) - Finnerty, Eoin; Ramasawmy, Rajiv; O'Callaghan, James; Connell, John J.; Lythgoe, Mark; Shmueli, Karin; Thomas, David L.; Walker‐Samuel, Simon
Abstract : Purpose: This preclinical study investigated the use of QSM MRI to noninvasively measure venous oxygen saturation (SvO2) in the hepatic and portal veins. Methods: QSM data were acquired from a cohort of healthy mice (n = 10) on a 9.4 Tesla MRI scanner under normoxic and hyperoxic conditions. Susceptibility was measured in the portal and hepatic veins and used to calculate SvO2 in each vessel under each condition. Blood was extracted from the inferior vena cava of 3 of the mice under each condition, and SvO2 was measured with a blood gas analyzer for comparison. QSM data were also acquired from a cohort of mice bearing liver tumors under normoxic conditions. Susceptibility was measured, and SvO2 calculated in the portal and hepatic veins and compared to the healthy mice. Statistical significance was assessed using a Wilcoxon matched‐pairs signed rank test (normoxic vs. hyperoxic) or a Mann‐Whitney test (healthy vs. tumor bearing). Results: SvO2 calculated from QSM measurements in healthy mice under hyperoxia showed significant increases of 15% in the portal vein ( P < 0.05) and 21% in the hepatic vein ( P < 0.01) versus normoxia. These values agreed with inferior vena cava measurements from the blood gas analyzer (26% increase). SvO2 in the hepatic vein was significantly lower in the colorectal liver metastases cohort (30% ± 11%) than the healthy mice (53% ± 17%) ( P < 0.05); differences in the portal vein were not significant. Conclusion: QSM is a feasible tool for noninvasively measuring SvO2 in the liver and can detect differences due to increased oxygen consumption in livers bearing colorectal metastases.